PR-Тонким слоем - Деревянко, Елена Георгиевна (My University, 2014)
В статье раскрыты вопросы управления репутацией и умения оценивать репутационные последствия деятельности. Акцентировано внимание на необходимости знания технологических аспектов репутационного менеджмента и ориентации на нормальную систему управления репутацией. Приведены примеры неудачных PR-кампаний. The article considers the issues of reputation management and the ability to assess the reputational consequences of activity. The author pays attention on the need of knowledge of reputational management’s technological aspects and the orientation on the normal system of reputation management. The author gives the examples of failed PR-campaigns.
Keywords: репутационный менеджмент; репутация; репутационный кризис; PR; reputation management; reputation; reputational crisis; PR